Association analysis revealed importance of dominance effects on days to silk of maize nested association mapping (NAM) population - MONIR Md. Mamun; ZHU Jun (浙江大学学报. 农业与生命科学版)
Full model and multi-loci additive model were used to analyze the days to silk (DS, female flowering) of maize nested association mapping (NAM) population. Analysis with the full model revealed that small effects of additive, dominance, epistasis, and their environmental interactions of many loci controlled the DS of maize NAM population. Dominance related effects had large impacts on the trait. Estimated total heritability was 79.86%, whereas 50.52% was due to dominance related effects. Environmental specific genetic effects also revealed as imperative for DS, explained 27.31% phenotypic variations. The highly significant (－log10 PEW>5) quantitative trait SNPs (QTSs) identified were 50 for full model, but 47 for additive model with low heritability (31.65%). Utilizing the association analysis results of DS, genotypes and total genetic effects of superior lines, superior hybrids were predicted that could be useful for future breeding program.